Detection of leptospires from experimentally infected hamsters by the polymerase chain reaction assay - A. Rashid, Fairuz Ridzlan; Bahaman, Abdul Rani; Bejo, Siti Khairani; Mutalib, Abdul Rahim (2012)
Leptospirosis outbreaks in humans in Malaysia have been frequently reported in 2010-2011. A study has managed to isolate several pathogenic strains from east region of Peninsular Malaysia. An isolate was inoculated into 21 hamsters to determine the pathogenicity of the isolate. The movement of the isolate was traced and it was detected at Day 3 post infection to be in the kidneys. The use of PCR assay is a reliable method to detect leptospires in the experimental animals and therefore in naturally infected animals as well.